Composite lymphoma of concurrent T zone lymphoma and large cell B cell lymphoma in a dog - Matsuyama, Arata; Bienzle, Dorothee; Richardson, Danielle; Deravi, Nariman; Hwang, Mei-Hua; Darzentas, Nikos; Keller, Stefan M (BMC veterinary research, 2019)
BACKGROUND: Evolution of indolent to aggressive lymphoma has been described in dogs but is difficult to distinguish from the de novo development of a second, clonally distinct lymphoma. Differentiation of these scenarios can be aided by next generation sequencing (NGS)-based assessment of clonality of lymphocyte antigen receptor genes. CASE PRESENTATION: An 8-year-old male intact Mastiff presented with generalized lymphadenomegaly was diagnosed with nodal T zone lymphoma (TZL) based on cytology, histopathology, immunohistochemistry and flow cytometry. Thirteen months later, the dog re-presented with progressive lymphadenomegaly, and based on cytology and flow cytometry, a large B cell lymphoma (LBCL) was diagnosed. Sequencing-based clonality testing confirmed the de novo development of a LBCL and the persistence of a TZL. CONCLUSIONS: The occurrence of two distinct lymphoid neoplasms should be considered if patient features and tumor cytomorphology or immunophenotype differ among sequential samples. Sequencing-based clonality testing may provide conclusive evidence of two concurrent and distinct clonal lymphocyte populations, termed most appropriately "composite lymphoma".
Keywords: difúzní velkobuněčný B-lymfom; hormonální protinádorové látky; Chlorambucil; alkylační protinádorové látky; psi; prednison; Lymphoma, T-Cell; Antineoplastic Agents, Alkylating; Dogs; Lymphoma; mužské pohlaví; Dog Diseases; Canine; Lymphoma, Large B-Cell, Diffuse; Clonality; nemoci psů; zvířata; PARR; Prednisone; Composite lymphoma; Antineoplastic Agents, Hormonal; lymfom T-buněčný; chlorambucil; Antigen receptor gene rearrangement; Lymphosarcoma; Dog; Male; Animals